Some Nonstrandard Result of Continuous, Monotonic Functions - I. Hamad (College of Education for Pure Sciences, 2005)
The aim of this paper is to use some concepts of nonstandard analysis given by Robinson, [8], and axiomatized by Nelson,E. [6] to present a new result of continuous and monotonic function when they are defined on nonstandard sets.